Do Patients Undergo Prostate Examination while Having a Colonoscopy? - Tess Hammett; Lawrence C Hookey; Jun Kawakami (Canadian Journal of Gastroenterology)
OBJECTIVES: To determine the rate at which physicians report performing a digital rectal examination and comment on the prostate gland before performing colonoscopy in men 50 to 70 years of age.